2016
DOI: 10.1016/j.riem.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Conductas de engaño de alumnos de primero y tercer año de Medicina

Abstract: Introducción: La carrera de Medicina debería atraer a estudiantes con altos valores morales. Las nuevas tecnologías y el acceso a la información facilitarían conductas de engaño, asimismo la experiencia académica del alumno también influiría. Objetivo: Comparar consideración, severidad, observación y realización de conductas de engaño y razones y consecuencias, manifestadas por alumnos de primero y tercer año de Medicina de la Universidad de Buenos Aires. Método: Diseño retrospectivo, transversal y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Researchers have examined academic dishonesty in a variety of contexts, including medicine (Kusnoor & Falik, 2013;Rancich et al, 2016), nursing (Macale et al, 2017;Park et al, 2013;Smedley, Cradwford, & Cloete, 2015), business management (Iberahim, Hussein, Samat, Noordin, & Daud, 2013;Tsui & Ngo, 2016), engineering (Vieyra, Strickland, & Timmerman, 2013;Yeo, 2007), psychology (Owens & White, 2013), etc. Findings yielded by these studies indicate that higher propensity for academic dishonest behaviour can be found among engineering students (Harding et al, 2004) and business students (Gallant et al, 2014;Passow, Mayhew, Finelli, Harding, & Carpenter, 2006).…”
Section: Framing the Current Study In The Context Of Academic Dishonestymentioning
confidence: 99%
“…Researchers have examined academic dishonesty in a variety of contexts, including medicine (Kusnoor & Falik, 2013;Rancich et al, 2016), nursing (Macale et al, 2017;Park et al, 2013;Smedley, Cradwford, & Cloete, 2015), business management (Iberahim, Hussein, Samat, Noordin, & Daud, 2013;Tsui & Ngo, 2016), engineering (Vieyra, Strickland, & Timmerman, 2013;Yeo, 2007), psychology (Owens & White, 2013), etc. Findings yielded by these studies indicate that higher propensity for academic dishonest behaviour can be found among engineering students (Harding et al, 2004) and business students (Gallant et al, 2014;Passow, Mayhew, Finelli, Harding, & Carpenter, 2006).…”
Section: Framing the Current Study In The Context Of Academic Dishonestymentioning
confidence: 99%